Effects of Neolamarckia cadamba Leaf Extract on Dynamic Fermentation Characteristics and Bacterial Community of Stylosanthes guianensis Silage - Huang, Peishan; Chen, Mengmeng; Chen, Dekui; Zang, Meiqi; Zhang, Weiling; Lin, Xiyue; Han, Hongyan; Zhang, Qing (Fermentation (Basel), 2024)
This study focused on exploring the effects of Neolamarckia cadamba leaf extract (NE) on the fermentation process and bacterial community of stylo (Stylosanthes guianensis) silage. Fresh raw materials of stylo were ensiled with 0%, 1%, and 2% NE, and various fermentation parameters, nitrogen components, and microbial compositions were analyzed at different time points (days 3, 7, 14, and 30) during the ensiling process. The experiment showed that, in comparison to the control group, incorporating NE into the ensiling process resulted in improved fermentation parameters, including increased lactic acid and acetic acid levels, as well as decreased pH, coliform population, and ammonia nitrogen concentration. Moreover, the relative abundances of Lactobacillus and Pediococcus were augmented, while the growth of Enterobacter was inhibited by the NE addition. These results suggest that NE has potential as a novel additive for silage, promoting a reduction in harmful bacteria and enhancements in the nutritional quality and fermentation characteristics of stylo silage.